PENERAPAN ETIKA BISNIS DALAM MELAKUKAN TRANSAKSI PENJUALAN CV. PERCETAKAN CITRA MEDAN MENURUT PERSPEKTIF ETIKA EKONOMI ISLAM - Atikah noor (Cemara Education and Science, 2023)
Business ethics in sales transactions from an Islamic Economic perspective are ethical principles that are implemented in business and sales transactions in accordance with Islamic principles. This research was conducted at CV. Citra Medan Printing as one of the MSME actors on Jalan Sisingamangaraja No. 33 KM. 6.1 Medan City. Qualitative research method with primary data sources consisting of the main director and CV owner. Citra Medan Printing, collectors / marketing, clients / customers and secondary consisting of financial documents, goods purchase invoices, sales invoices. Data analysis by collecting, selecting and making decisions. The data was then triangulated both between data and between informants. The findings of this research are business ethics in sales transactions carried out by CV. Medan Image Printing is enforcing the prohibition on trading in prohibited goods, being correct, trustworthy, honest, upholding justice and forbidding interest, enforcing compassion and forbidding monopoly, upholding tolerance and brotherhood. To improve the economy of Muslims, it is hoped that CV. Citra Medan Printing is building more connectivity with Muslim entrepreneurs and Muslim investors so that the economy in the printing sector can be controlled by Muslims.